IMPLEMENTATION OF THE CONTEXTUAL TEACHING AND LEARNING MODEL IN IPS COURSES AT CLASS V SDN SINEY - Muchdar Muchdar; Arif Firmansyah (Universitas Tadulako, 2022)
The problem of IPS learning in SDN Siney, can be said is still not varied in applying the methods and learning models that can be applied in IPS lesson in class V. Involve students in various learning process, identify, ask questions, and answer questions from students' IPS learning experience. The students listened more and waited for the presentation from the teacher rather than finding and finding their own knowledge and skills needed. This situation has an impact on students' learning outcomes in IPS lessons in class V, that is average reaching only 60%, this does not reach the value of the minimum criteria of students, that is 65%. The main purpose of this research is to develop the IPS learning tool. This type of research is research development (research and development) with four stages 4-D define, design, develop, and disseminate. The results showed that learning tools developed to support the learning process of social studies, seen from the activities teachers implement lesson plans 2.60% to 4% with good criteria, Contextual Teaching And Learning components that appear on the learning activities of students that is learning 3.33%, reflection 3.13%, modeling 3,06%, authentic assessment 2,88%, constructivism 2,84%, inquiry 2,81%, asking question 2,63% with good criterion, student response to learning process implemented, and device used 90% express happy, the result of student completion based on the score reached above 75% of minimum score, and instrument characteristic used reliability 0,75 and sensitivity of item 0,30 with complete criterion. Thus, the learning process of IPS material Appreciate the services and the role of the struggle in proclaiming independence through the seven components Contextual Teaching and Learning positively influence the student activity during the teaching and learning process in the classroom, improving students' positive responses to the process of teaching and learning activities, the learning process well done , and improve student learning outcomes.